Visible-light induced metal-free cascade Wittig/hydroalkylation reactions. Issue 4 (18th February 2021) - Miao, Pannan; Li, Ruining; Lin, Xianfeng; Rao, Liangming; Sun, Zhankui
Abstract : Through a relay olefination and radical addition process, we developed cascade Wittig/hydroalkylation reactions induced by visible light. This metal-free radical approach features mild conditions, robustness, and excellent functionality tolerance. Abstract : Cascade reactions are green and powerful transformations for building multiple carbon–carbon bonds in one step. Through a relay olefination and radical addition process, we were able to develop the cascade Wittig/hydroalkylation reactions induced by visible light. This metal-free radical approach features mild conditions, robustness, and excellent functionality compatibility. It allows access to saturated C3 homologation products directly from aldehydes or ketones. The synthetic utility of this method is demonstrated by a two-step synthesis of indolizidine 209D .